Conditions for the existence of Kelvin-Helmholtz instability in a CME. Issue Volume 11:Issue S320(2015) (9th September 2016) - Páez, Andrés; Jatenco-Pereira, Vera; Falceta-Gonçcalves, Diego; Opher, Merav
Abstract: The presence of Kelvin-Helmholtz instability (KHI) in the sheaths of Coronal Mass Ejections (CMEs) has been proposed and observed by several authors in the literature. In the present work, we assume their existence and propose a method to constrain the local properties, like the CME magnetic field intensity for the development of KHI. We study a CME in the initiation phase interacting with the slow solar wind (Zone I) and with the fast solar wind (Zone II). Based on the theory of magnetic KHI proposed by Chandrasekhar (1961 ) we found the radial heliocentric interval for the KHI existence, in particular we constrain it with the CME magnetic field intensity. We conclude that KHI may exist in both CME Zones but it is perceived that Zone I is more appropriated for the KHI formation.